1999
DOI: 10.1109/77.783643
|View full text |Cite
|
Sign up to set email alerts
|

First results for a novel superconducting imaging-surface sensor array

Abstract: RECEIVEDAbstract-A superconducting imaging-surface system was constructed using 12 coplanar thin-am SQUID magnetometers located parallel to and spaced 2 cm from a 25 cm diameter l a d imaging-plane. Some measurements included two additional sensors on the "back" side of the superconducting imaging-plane to study the field symmetry for our system. Performance was measured in a shielded can and in the open laboratory environment. Data from this system has been used to: (a) A phantom source field was measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…As in the case of MEG systems, some innovative proposals have been introduced with the aim at simplifying the system design and thus reducing the related costs and improving the information obtained by recording of the magnetic field. Promising preliminary results obtained with a flat 12-channel system based on a superconducting imaging surface have been presented [108]. The basics of system operation are similar to the concepts described for the helmet system in section 7.1.1; with this method virtual axial gradiometers are determined by the effect of the superconducting surface, thus avoiding fabrication and balancing costs.…”
Section: 13mentioning
confidence: 93%
See 2 more Smart Citations
“…As in the case of MEG systems, some innovative proposals have been introduced with the aim at simplifying the system design and thus reducing the related costs and improving the information obtained by recording of the magnetic field. Promising preliminary results obtained with a flat 12-channel system based on a superconducting imaging surface have been presented [108]. The basics of system operation are similar to the concepts described for the helmet system in section 7.1.1; with this method virtual axial gradiometers are determined by the effect of the superconducting surface, thus avoiding fabrication and balancing costs.…”
Section: 13mentioning
confidence: 93%
“…Moreover, the superconducting surface acts as shielding for the near sensors, deviating the magnetic field generated by far sources, thus requiring a low-quality shielded room for proper operation. A whole-head system comprising 155 dcSQUID integrated magnetometers and a hemispherical imaging surface made of lead is being developed [107]. The sensors are dcSQUID integrated magnetometers [108]; due to the different geometry of the superconducting and measurement surfaces, the resulting gradiometers have different baselines.…”
Section: Multichannel Systems For Megmentioning
confidence: 99%
See 1 more Smart Citation
“…The other is a magnetoencephalography system using 155 SQUID magnetometers and a lead hemispherical S1S of radius 11 cm. Tests of these systems indicated that when the SQUIDS were near the center of the S1S they dld behave primarily as gra&ometers [2].…”
Section: Introductionmentioning
confidence: 99%
“…low signal-to-noise, cost, bulk). The Los Alamos SIS-MEG system [3] is based on the principal that Meissner currents flow in the surface of superconductors, preventing any significant penetration of magnetic fields. A hemispherical SIS with a brim, or helmet, surrounds the SQUID sensors largely shielding them from sources outside the helmet while measuring fields from nearby sources within the helmet.…”
Section: Introductionmentioning
confidence: 99%